Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.2174/1574891x11666160201122236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Dose Oral Vitamin-D and Calcium Replacement in HIV Patients

Abstract: After 12 months of follow up, replacement of low dose once daily oral vitamin-D with calcium in treatment experienced HIV patients with vitamin-D deficiency can increase vitamin-D level, reduce PTH level without any change in BMD of hip and spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Conesa-Botella et al (15) showed that vitamin D deficiency was common before highly active antiretroviral therapy (HAART) and after 12 months on HAART, vitamin D level had a significant decrease. After a 12 months follow-up, replacement of low dose once daily oral vitamin D with calcium in treatment-experienced HIV patients with vitamin D deficiency can elevate the vitamin D level (23).…”
mentioning
confidence: 99%
“…Conesa-Botella et al (15) showed that vitamin D deficiency was common before highly active antiretroviral therapy (HAART) and after 12 months on HAART, vitamin D level had a significant decrease. After a 12 months follow-up, replacement of low dose once daily oral vitamin D with calcium in treatment-experienced HIV patients with vitamin D deficiency can elevate the vitamin D level (23).…”
mentioning
confidence: 99%
“…Yet, it is important that this does not allow identification of causal relations, as low levels of 25(OH) D can be seen as both, cause or consequence of sHPT, since high PTH levels can decrease 25(OH)D concentrations by increasing 1-hydroxylation [5]. Nevertheless, it has been well-established that vitamin D is important in maintaining calcium homeostasis and vitamin D supplementation has been demonstrated to lower PTH levels [23][24][25]. Interestingly, in our cohort there was no significant difference in the prevalence of sHPT in patients with or without vitamin D supplementation (13.6 % vs. 16.7 %, p = 0.132; data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This means, that in about 95 % of patients with elevated PTH levels, we were able to identify risk factors that could be targeted quite easily by therapeutic interventions. But while there is evidence for positive effects of compensation of hypocalcemia and supplementation of 25(OH)D on sHPT in general populations as well as in HIV-infected populations [23][24][25]40], prospective data about effects of switching from TDF to non-TDF-containing ART on PTH levels are missing. This data seems important as it could help us identify patients at risk for low BMD on TDF but also patients at low risk of bone related complications on TDF-containing ART, and therefore might help us to avoid ART-switches in patients on a stable, well-tolerated therapy.…”
Section: Discussionmentioning
confidence: 99%